2021
DOI: 10.3390/children8121096
|View full text |Cite
|
Sign up to set email alerts
|

Parental Pesticide Exposure and Childhood Brain Cancer: A Systematic Review and Meta-Analysis Confirming the IARC/WHO Monographs on Some Organophosphate Insecticides and Herbicides

Abstract: Background: Brain tumors are the second most common neoplasm in the pediatric age. Pesticides may play an etiologic role, but literature results are conflicting. This review provides a systematic overview, meta-analysis, and IARC/WHO consideration of data on parental exposure to pesticides and childhood brain tumors. Methods: We searched PubMed, SCOPUS, and Google Scholar for literature (1 January 1966–31 December 2020) that assessed childhood brain tumors and parental exposure to pesticides. We undertook a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…A variety of pesticides are prohibited because they are not biodegradable and impact human health [ 162 ]. Chemical pesticides were also identified as causing birth defects in children and cancer [ 163 , 164 ]. The contamination of organochloride pesticides in food products and water are also concerning, due to the danger in long-range transport, bioaccumulation in human and animal tissue, and biomagnification in food chains [ 165 ].…”
Section: Nanotechnology In Food Monitoringmentioning
confidence: 99%
“…A variety of pesticides are prohibited because they are not biodegradable and impact human health [ 162 ]. Chemical pesticides were also identified as causing birth defects in children and cancer [ 163 , 164 ]. The contamination of organochloride pesticides in food products and water are also concerning, due to the danger in long-range transport, bioaccumulation in human and animal tissue, and biomagnification in food chains [ 165 ].…”
Section: Nanotechnology In Food Monitoringmentioning
confidence: 99%
“…The toxicity to human and other non-target species may be due to their poor selectivity to target species and the similarities of all organisms in the basic biological processes. As a result, the International Agency for Research on Cancer (IARC) classified some pesticides, such as diazinon, glyphosate, and malathion (8, 9), being possible human carcinogens as shown in human epidemiological studies and experimental animal data, and the use of various pesticides were banned or strictly regulated (e.g. US-EPA, Dir.…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate exposure has been linked to an increased risk of non-Hodgkin’s lymphoma, endocrine disruptions, and chromosomal damage [ 4 , 5 ]. Feulefack et al [ 6 ] confirmed an association between prenatal exposure to organophosphate herbicides and childhood brain tumors. Although glyphosate application has been banned or regulated in many countries, its usage and human exposure to glyphosate-based herbicides continue to rise.…”
Section: Introductionmentioning
confidence: 99%